2016
DOI: 10.1111/mec.13913
|View full text |Cite
|
Sign up to set email alerts
|

Clockgene polymorphism, migratory behaviour and geographic distribution: a comparative study of trans‐Saharan migratory birds

Abstract: Migratory behaviour is controlled by endogenous circannual rhythms that are synchronized by external cues, such as photoperiod. Investigations on the genetic basis of circannual rhythmicity in vertebrates have highlighted that variation at candidate 'circadian clock' genes may play a major role in regulating photoperiodic responses and timing of life cycle events, such as reproduction and migration. In this comparative study of 23 trans-Saharan migratory bird species, we investigated the relationships between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(51 citation statements)
references
References 88 publications
(260 reference statements)
3
46
2
Order By: Relevance
“…These studies give important leads to identifying the physiological organization of the timing of migration and the interactive roles of different physiological systems. Other studies have looked at genetic differentiation of populations that differed in migratory phenotype, such as the timing or direction of their journeys 27,169,170 . Several studies indicate evolutionary changes that are associated with the timing of migration 25,171 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies give important leads to identifying the physiological organization of the timing of migration and the interactive roles of different physiological systems. Other studies have looked at genetic differentiation of populations that differed in migratory phenotype, such as the timing or direction of their journeys 27,169,170 . Several studies indicate evolutionary changes that are associated with the timing of migration 25,171 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies indicate evolutionary changes that are associated with the timing of migration 25,171 . It is now entirely feasible to combine tracking data with molecular information, such as differences in candidate genes that based on mechanistic studies in chronobiology are predicted to influence migratory timing, even if suspected links currently are still often tenuous 170 . A concurrent challenge, however, for efficient data-mining of bird tracking information, is development of sound theoretical frameworks within migration biology (e.g., 58,67,172 , and what the potential consequences of mismatches across annual cycle stages exist (but see, 75,79 for examples in birds, and 174,175 for examples in mammals).…”
Section: Discussionmentioning
confidence: 99%
“…In birds, migratory timing appears to be controlled in concert with timing of reproduction and moult by a circannual clock in both wild populations and caged birds (Gwinner, 2003;Visser et al, 2010). Correlative studies using a candidate gene approach identified the Clock gene as a possible candidate for migratory timing (Peterson et al, 2013;Bazzi et al, 2015Bazzi et al, , 2016Saino et al, 2017;Contina et al, 2018). The otherwise highly conserved Clock gene shows length variation at a poly-glutamine repeat, and shorter alleles have been associated with earlier arrival times at the breeding grounds in barn swallows (Bazzi et al, 2015).…”
Section: Accurate Phenotyping Of Migratory Behaviour Is Keymentioning
confidence: 99%
“…Such a short circannual period is consistent with gonadal recrudescence starting in late autumn in house sparrows, perhaps an adaptation to high territorial competition in a sedentary bird (Hegner & Wingfield, ). In contrast, precise timing will be particularly important for long‐distance migrants, and especially extreme “long‐jump” migrants, of which Arctic‐breeding shorebirds are a typical example (Åkesson et al., ; Bazzi et al., ; Conklin, Senner, Battley, & Piersma, ; Helm, Gwinner, & Trost, ; Piersma, ). For these species, environmental cues at departure from equatorial or temperate wintering sites are uninformative of the phenological conditions at remote Arctic breeding grounds (Piersma et al., ; Winkler, Jørgensen, et al., ).…”
Section: Discussionmentioning
confidence: 99%